(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2024)
The critical role of education in fostering sustainability awareness is highlighted in this study, which aims to prepare students as responsible citizens in a sustainable future. The study reported students’ sustainability awareness in the context of renewable energy across the three sustainability pillars: economic, social, and environmental. Data from 108 high school students, collected through a questionnaire measuring three dimensions (knowledge, attitudes, and behaviors), has revealed a need for enhanced educational strategies. These strategies are crucial to bridge the gap between sustainability knowledge and actionable practices. The findings not only contribute to the broader Education for Sustainable Development (ESD) discourse but also provide localized insights that can potentially shape and inform future educational and policy interventions, offering hope for a more sustainable future.